2010
DOI: 10.4269/ajtmh.2010.10-0154
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Malaria Risk in Bangladesh Using Bayesian Geostatistical Models

Abstract: BACKGROUNDBecause of the wide range of vectors able to transmit malaria, each with unique ecological requirements, malaria is transmitted in a wide range of eco-epidemiological settings. The disease can be coarsely grouped into four such settings: malaria of deep forests, forest fringe, and hills; rural malaria attributable to water-resources development (e.g., irrigation and large dams); rural malaria attributable to wetlands, rivers, streams, coasts, and non-agricultural manmade habitats; and urban and peri-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 43 publications
0
40
0
Order By: Relevance
“…1). Following baseline entomological surveys to describe the distribution of the vector Anopheles farauti (The PacMI Survey Group on behalf of the Ministries of Health of Vanuatu and Solomon Islands, 2010) and geo-statistical analysis of malaria survey data on the main island of Tanna in 2008 (Reid et al, 2010), focal IRS operational areas on Tanna was defined as all settlements located within a 2 km boundary of the coastline. As part of the Tafea province elimination strategy, three annual rounds of IRS were planned for the Tanna focal IRS zone between 2009 and 2011.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…1). Following baseline entomological surveys to describe the distribution of the vector Anopheles farauti (The PacMI Survey Group on behalf of the Ministries of Health of Vanuatu and Solomon Islands, 2010) and geo-statistical analysis of malaria survey data on the main island of Tanna in 2008 (Reid et al, 2010), focal IRS operational areas on Tanna was defined as all settlements located within a 2 km boundary of the coastline. As part of the Tafea province elimination strategy, three annual rounds of IRS were planned for the Tanna focal IRS zone between 2009 and 2011.…”
Section: Study Areamentioning
confidence: 99%
“…Lozano-Fuentes et al, 2008;Clements et al, 2009;Daash et al, 2009;Reid et al, 2010). In the context of malaria elimination, the need for modernized, high-resolution mapping to support the operational management of scaled-up interventions is also recognized (The malEra Consultative Group on Monitoring Evaluation and Surveillance, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, both timely and accurate diagnosis as well as the benefits of testing before commencement of malaria treatment should be emphasized. Regularly updated malaria risk maps (Haque et al, 2010b;Reid et al, 2010Reid et al, , 2012Haque et al, 2011;Wang et al, 2014) can help the NMCC to monitor progress and mobilize resources. Distance, population density, treatment seeking behavior and other health facilities should be considered (Ahmed et al, 2009;Haque et al, 2012;Simon et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In another paper 8 , the authors concluded that the dynamics and seasonal abundance of malaria vectors in the Kintampo area of Ghana were influenced by microecology, rainfall, and temperature patterns. Reid et al 9 considered the use of Bayesian geostatistical models in mapping the malaria risk in Bangladesh. In all these studies, it is important to point out that the presence of different socioeconomic factors could have had great impact on the spread of malaria during that time.…”
Section: Methodsmentioning
confidence: 99%